Automatic stabilizers, economic crisis and income distribution in Europe - Mathias Dolls; Clemens Fuest; Andreas Peichl (Institute for the Study of Labor (IZA), 2010)
This paper investigates to what extent the tax and transfer systems in Europe protect households at different income levels against losses in current income caused by economic downturns like the present financial crisis. We use a multi country micro simulation model to analyse how shocks on market income and employment are mitigated by taxes and transfers. We find that the aggregate redistributive effect of the tax and transfer systems increases in response to the shocks. But the extent to which households are protected differs across income levels and countries. In particular, there is little stabilization of disposable income for low income groups in Eastern and Southern European countries.
Keywords: E32; E63; H2; H31; 330; Automatic stabilization; crisis; inequality; redistribution; Eingebauter Stabilisator; Steuersystem; Sozialtransfer; Wirtschaftskrise; Verteilungswirkung; Vergleich; EU-Staaten; EU-Staaten (Osteuropa)